2010
DOI: 10.12697/sss.2010.38.1-4.11
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal iconicity: A cognitive semiotic approach to sound symbolism

Abstract: It is being increasingly recognized that the Saussurean dictum of “the arbitrariness of the linguistic sign” is in conflict with the pervasiveness of the phenomenon commonly known as “sound symbolism”. After first presenting a historical overview of the debate, however, we conclude that both positions have been exaggerated, and that an adequate explanation of sound symbolism is still lacking. How can there, for example, be (perceived) similarity between expressions and contents across different sensory modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 39 publications
7
108
1
3
Order By: Relevance
“…This is in marked contrast to other recent studies which have made broader efforts to examine specific properties of linguistic sound underlying the effect in a controlled way (e.g. D 'Onofrio, 2013;Aveyard, 2012;Nielsen & Rendall, 2011;Ahlner & Zlatev, 2010;Westbury, 2005). Thus, Bremner et al (2013) show that a nonliterate population makes some broad word-shape associations, but it remains unclear which specific phonetic qualities underlie these associations.…”
Section: Non-literate Children Cross-cultural Studies and Methodologcontrasting
confidence: 62%
See 3 more Smart Citations
“…This is in marked contrast to other recent studies which have made broader efforts to examine specific properties of linguistic sound underlying the effect in a controlled way (e.g. D 'Onofrio, 2013;Aveyard, 2012;Nielsen & Rendall, 2011;Ahlner & Zlatev, 2010;Westbury, 2005). Thus, Bremner et al (2013) show that a nonliterate population makes some broad word-shape associations, but it remains unclear which specific phonetic qualities underlie these associations.…”
Section: Non-literate Children Cross-cultural Studies and Methodologcontrasting
confidence: 62%
“…Nielsen and Rendall (2012) made the first attempt to systematically control for orthographic angularity. They found that non-words containing sonorants were preferentially paired with rounded shapes, versus obstruents (see also, Ahlner & Zlatev, 2010). To remove orthographic influence, Nielsen and Rendall (2012) capitalised the first letter in their non-words, thereby altering the curvature of some sonorants from rounded to angular (e.g.…”
Section: Non-literate Children Cross-cultural Studies and Methodologmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the stuff of which metaphors are made. (See Sonesson 1989, 2010. Interpreted in another way, it is the point of departure of the distinction which is basic to cultural semiotics.…”
Section: Iconicity In Language and Picturesmentioning
confidence: 99%